2014
DOI: 10.2741/4234
|View full text |Cite
|
Sign up to set email alerts
|

The role of PGRN in musculoskeletal development and disease

Abstract: Progranulin (PGRN) is a growth factor that has been implicated in wound healing, inflammation, infection, tumorigenesis, and is most known for its neuroprotective and proliferative properties in neurodegenerative disease. This pleiotropic growth factor has been found to be a key player and regulator of a diverse spectrum of multi-systemic functions. Its critical anti-inflammatory role in rheumatoid arthritis and other inflammatory disease models has allowed for the propulsion of research to establish its signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 80 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…In addition, PGRN can suppress TNFa-induced ADAMTS-7 and ADAMTS-12 production through binding to TNFR receptors. It was demonstrated that PGRN and its engineered derivative, Attstrin could restrain TNFa-induced release of inflammatory and catabolic mediators, including MMP-13, RUNX2, COX-2 and iNOS in human chondrocytes in vitro, and promote the synthesis of ECM integrating components, such as Col 2 and Aggrecan [15,42]. Several studies have validated that PGRN knock-out accelerated OA progress [16,43,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PGRN can suppress TNFa-induced ADAMTS-7 and ADAMTS-12 production through binding to TNFR receptors. It was demonstrated that PGRN and its engineered derivative, Attstrin could restrain TNFa-induced release of inflammatory and catabolic mediators, including MMP-13, RUNX2, COX-2 and iNOS in human chondrocytes in vitro, and promote the synthesis of ECM integrating components, such as Col 2 and Aggrecan [15,42]. Several studies have validated that PGRN knock-out accelerated OA progress [16,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Articular chondrocytes apoptosis and cartilage loss in the knee joint of surgically induced OA rats were also ameliorated by the injection of miR-29b-3p antagomir, demonstrated by TUNEL and safranin O-fast green staining. This work showed miR-29b-3p facilitates chondrocyte apoptosis and OA by targeting PGRN, and miR-29b-3p or PGRN may be the potential target for OA treatments.indicating that miR-29b-3p may play an important role in the occurrence and development of OA.Progranulin (PGRN) is a growth factor expressed by a variety of cells types, including epithelial cells, neurons, macrophages and chondrocytes [15] and has been proven to play a role in various physiological processes, such as wound healing, tumourigenesis and neurodegenerative disease. Moreover, PGRN was also implicated in the pathogenesis of OA.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…GEP contains seven-and-a-half repeats of a cysteine-rich motif in the order P-G-F-B-A-C-D-E [ 46 ]. GEP was highly expressed in chondrocytes of the musculoskeletal system [ 47 ] and played a key role in musculoskeletal development and diseases [ 48 ]. Recent reports suggested that GEP played a protective role in surgically induced OA [ 49 , 50 ] and inflammatory arthritis [ 46 ].…”
Section: Adamts-7mentioning
confidence: 99%
“…Ultrastructural studies show that PGRN is a polypeptide chain composed of 593 amino acid residues with an intracellular molecular weight of approximately 68.5 kDa, which becomes an 88 kDa secreted form following glycosylation . The PGRN polypeptide chain contains 7.5 tandem repeats of a highly conserved 12 cysteine (Cys)‐rich motif (CX 5–6 CX 5 CCX 8 CCX 6 CCXDX 2 HCCPX 4 CX 5–6 C) in the order P‐G‐F‐B‐A‐C‐D‐E, where A‐G are full repeats and P is one half‐motif (Figure ). The human gene coding PGRN is composed of 13 exons and is located within the long arm of chromosome 17 (17q21.32) .…”
Section: Introductionmentioning
confidence: 99%